PENGELOLAAN SUMBER DAYA INSANI DAN KEUANGAN DALAM MENINGKATKAN AKUNTABILITAS PADA SEKOLAH DASAR ISLAM AL- BAYANI CIKARANG - Taryaman, Tantan; Hermawan, Agung (STEBI Global Mulia Cikarang, 2021)
Management can easily be understood as a sequence of activities in terms of planning and decision making that can be directed to resources within the organization in achieving organizational goals effectively and efficiently. Human resource management must be managed properly in an effort to increase organizational effectiveness and efficiency in a company, and this is one of the most important factors for the organization. This research aims to find out whether MSDI practices such as recruitment, selection, performance appraisal, training and development, and compensation are based on Islamic values and to find out whether financial management at Al-Bayani Cikarang Islamic Elementary School is in accordance with these values. Islamic values as the system adopted. The theory adopted in this study uses data analysis which is carried out in steps such as collecting, reducing data, presenting data and drawing conclusions. This research was conducted using a qualitative research approach. Qualitative research is conducted to build knowledge through understanding and discovery. As for the research results obtained, in carrying out MSDI practices the institution has implemented Islamic values in accordance with Islamic law as outlined in the vision and mission of the institution. As time goes by and the development of the era, the school begins to follow current developments, financial management has been carried out systematically, which is carried out with banks. However, in my opinion, even though the school has collaborated with the bank, the two banks are not Islamic banks.